Quasi-1D XY antiferromagnet Sr2Ni(SeO3)2Cl2 at Sakai-Takahashi phase diagram - Kozlyakova, Ekaterina; Moskin, A. V.; Berdonosov, P. S.; Gapontsev, V. V.; Streltsov, S. V.; Uhlarz, M.; Spachmann, Sven; Elghandour, Ahmed; Klingeler, Rüdiger; Vasiliev, A. N. (Scientific reports, 2021)
Uniform quasi-one-dimensional integer spin compounds are of interest as a potential realization of the Haldane conjecture of a gapped spin liquid. This phase, however, has to compete with magnetic anisotropy and long-range ordered phases, the implementation of which depends on the ratio of interchain J′ and intrachain J exchange interactions and both uniaxial D and rhombic E single-ion anisotropies. Strontium nickel selenite chloride, Sr2Ni(SeO3)2Cl2, is a spin-1 chain system which passes through a correlations regime at Tmax ~ 12 K to long-range order at TN = 6 K. Under external magnetic field it experiences the sequence of spin-flop at Bc1 = 9.0 T and spin-flip transitions Bc2 = 23.7 T prior to full saturation at Bsat = 31.0 T. Density functional theory provides values of the main exchange interactions and uniaxial anisotropy which corroborate the experimental findings. The values of J′/J = 0.083 and D/J = 0.357 place this compound into a hitherto unoccupied sector of the Sakai-Takahashi phase diagram.
Im Text ist "2", "3", "2" und "2" tiefgestellt
Gesehen am 15.10.2021